DAMPAK KEBIJAKAN PENGENAAN TARIF IMPOR DAGING SAPI TERHADAP KESEJAHTERAAN MASYARAKAT - Dwi Haryono (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2007)
The research aim is to analyze the impact of import tarrif policy of beef to the social welfare, especially to the breeder as a producer and consumer of beef. Classical Welfare Analysis (CWA) model was used as analyze method using supply and demand analyze. The result shows that the impact of import tarrif policy of beef tends to increase the local beef price. the far impact increased the producarea welfare, on the other hand the consumerae walfare decreased